Experimental Study of the Debris Flow Slurry Impact and Distribution - Haixin Zhao; Lingkan Yao; Yong You; Baoliang Wang; Cong Zhang (Shock and Vibration)
In this study, we present a new method to calculate debris flow slurry impact and its distribution, which are critical issues for designing countermeasures against debris flows. There is no unified formula at present, and we usually design preventive engineering according to the uniform distribution of the maximum impact force. For conducting a laboratory flume experiment, we arrange sensors at different positions on a dam and analyze the differences on debris flow slurry impact against various densities, channel slopes, and dam front angles. Results show that the force of debris flow on the dam distributes unevenly, and that the impact force is large in the middle and decreases gradually to the both sides. We systematically analyze the influence factors for the calculation of the maximum impact force in the middle point and give the quantitative law of decay from the middle to the sides. We propose a method to calculate the distribution of the debris flow impact force on the whole section and provide a case to illustrate this method.